Managing a Flow Line with Single-Kanban, Dual-Kanban or Conwip - YANG, Kum Khiong (Institutional Knowledge at Singapore Management University, 2000)
To control the production of different parts on a single flow line, managers can choose between the Single-kanban, Dual-kanban, and Conwip. This paper therefore compares the three different systems. The results show that Conwip consistently produces the shortest mean customer wait time and lowest total work-in-process. Our results also contradict the finding of a previous study, which showed that Dual-kanban performed better than Single-kanban. The different findings can, however, be attributed to the use of a material transfer policy, which favors the Dual-kanban modeled in the previous study. Our study shows that transferring replenished containers immediately to downstream stations, increasing the number of cards, and reducing the withdrawal cycle reduce the mean customer wait time significantly.